COVERAGE OF POLITICIAN’S IMAGE ON SOCIAL NETWORKS - Mirpulatov Behzod Sherzod o`g`li (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the writer highlighted the basic facts about the importance of creating image and demonstrating it by the help of social media for political leaders in modern society. In addition to this, while reading this article you will be able to get acquainted with advantages of media in development of political leadership.